The inclusion of Mexican cultural heritage through the pedagogies of indigenous peoples as shared values in teacher training programs - Herrera Labra, Graciela; Salazar Muro, María de Jesús (Clio. History and History Teaching, 2018)
The purpose of the article is to justify why it is important to include the pedagogies of native peoples in teacher education programs of basic education at the national level, as shared values of their tangible and intangible cultural heritage. This cultural heritage is the historical pillar of Mexico, which of course is not found only in the original peoples, but responds to a determined social historical process of the nation and that, in spite of the European conquest, continued to prevail in the pedagogies and values of the original peoples. We propose to crystallize these cultural patrimonies of native peoples to be considered as their own pedagogies in teacher training programs and from this field of formation to share cultural values through their knowledge, wisdom and cultural practices that have prevailed throughout history. and that account in the plans and programs of study with equality and cultural equity in the National Educational System. Likewise, the processes of contradiction that indigenous peoples have lived and have assumed throughout educational policies aimed at indigenous education are exposed. Finally, some considerations are raised for these teacher training programs.